Quota Brokers. (IMF Working Papers; Working Paper ;, 2004)
This paper examines the role of middlemen (brokers) in an imperfect secondary market for quota licenses. Middlemen facilitate trade when markets are thin, as potential buyers and sellers find it difficult to meet and transact directly. However, in thin markets, middlemen also have the ability to influence the terms on which trades occur, and the wedge they create between the buying and selling price limits the extent to which they facilitate trade. We develop and simulate a model of quota broker behavior to examine their welfare implications.